1992
DOI: 10.1136/adc.67.7_spec_no.779
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus prevalence in pregnant women: the influence of parity.

Abstract: Over 20 000 women attending for antenatal care at three London hospitals were prospectively studied to determine the prevalence of cytomegalovirus (CMV) antibodies; 54-40/ of these women were CMV seropositive. Ethnic group was strongly associated with CMV status: 45*9%/e of white women were seropositive, 88-2% ofAsian, and 77*2% ofblack women (African/Caribbean ethnic origin). Among 12 159 white women born in the British Isles, seropositivity was independently associated with increasing parity, older age, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
72
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 36 publications
(4 reference statements)
13
72
1
3
Order By: Relevance
“…This finding is contrary to a study among pregnant women in London which reported high (88.2%) seroprevalence in first pregnancies among women. 25 The high seroprevalence we observed could be due to reactivation or re-infection with different strains of CMV. Most Nigerian women have more than one child and love to be around children from other families even when they are pregnant, some shedding the virus, which underscores the problem of silent viral infection during pregnancy.…”
Section: Discussionmentioning
confidence: 80%
“…This finding is contrary to a study among pregnant women in London which reported high (88.2%) seroprevalence in first pregnancies among women. 25 The high seroprevalence we observed could be due to reactivation or re-infection with different strains of CMV. Most Nigerian women have more than one child and love to be around children from other families even when they are pregnant, some shedding the virus, which underscores the problem of silent viral infection during pregnancy.…”
Section: Discussionmentioning
confidence: 80%
“…In recent years, more and more cases of CMV infection of the anterior segment have been recognized in immunocompetent people also. In developed countries, the seroprevalence of CMV is approximately 50%, whereas it is approximately 90% in lessdeveloped regions [1][2][3][4]. Hence, not surprisingly, most of these cases have been from Asian countries, where there is a large reservoir of dormant CMV.…”
mentioning
confidence: 99%
“…13,14 Maternal seroprevalence depends on age, socioeconomic status, and parity. [15][16][17] But between industrialized countries there are clear differences in prevalence, probably because of race-bound predilection in addition to differences in sexual behavior, day care attendance, breastfeeding, and profession. 18,19 Spreading of CMV occurs through close contact with infected body fluids.…”
mentioning
confidence: 99%